Preventive aspects and patient satisfaction with laser aided gingivectomy versus conventional method. An in-vivo comparative study - Aras Maruf Rauf; Ara Omer Fattah (Erbil Dental Journal)
Background and Objectives: Nowadays, the field of dentistry has undergone an outstanding remarkable advances in both scientific and technological aspects, dentists are obligated to synchronize the progressive demands of the patients. Gingival diseases are among the most common health problems of human being. Gingivectomy, as a surgical interference can be performed with either scalpel or soft tissue Laser The objective of this study was to evaluate the preventive extent of Diode Laser in regards to gingivectomy associated complications beside the patient`s satisfaction. Methods: This in vivo comparative study was designed to include 64 patients, divided into 2 groups of patients treated with either Laser therapy (34 Patients) or conventional method (30 Patients) of gingivectomy. The outcomes of the study plus patients` satisfaction with each procedure were analyzed using IBM SPSS V. 22 program. Results: The mean age of the sample was 25.01 + 6.56 years, more than half (57.8%) of the sample were females. All the patients in the surgery group needed local anesthesia and periodontal pack compared to 23.5% and 0% of patients in the laser group respectively. The bleeding was significantly more severe in the first group than second group. The mean ranks of the post-operative pain scores among patients of the surgery group were significantly higher than laser group (p < 0.001). More than forty percent of the patients in the laser group were strongly satisfied with the procedure compared to 10% of patients in the surgery group. Conclusions: Diode laser can be used as a preventive tool for undesired Gingivectomyassociated pain, bleeding, and needs for anaesthesia which subsequently leads to more patient satisfaction compared to conventional methods.